Smart Village: An Effort to Implement District Digitalization to Support Public Services in Pleret Kapanewon Pleret District Bantul District - Suwarjo, Suwarjo (POPULIKA, 2025)
Village digitalization is an effort by the Pleret Village Government to realize a Smart Village. Providing access to online population administration services is one of the goals of village digitalization. Access to services that can be done from anywhere is expected to make services easy and efficient. The provision of online public services faces challenges if the community does not have internet access or does not master the application. This study aims to analyze the implementation of village digitalization in Pleret Village in providing online public services. This study uses a qualitative descriptive approach method with informants from service providers and service recipients. Triangulation is used to test the validity of the data obtained before being presented. The results of the study show that efforts to digitize Pleret Village have been well prepared. Village digitalization utilizes websites, public service applications and social media platforms that are fully supported by human resources, budgets and adequate infrastructure. Digitalization in public services provides easy access to services for the community. Residents can access services from anywhere so that they are efficient in terms of time and energy. However, some people still choose offline services by coming directly to the Pleret Village Office for several reasons, such as not understanding the online service features, not having an android, fast offline services and others. Keywords: Village Digitalization, Smart Village, Online Services.